Considerations on the preliminary safety assessment for operation of the melting facility for radioactive metal waste from nuclear facilities. (15th September 2022) - Jeong, KwanSeong; Roh, ChangHyun; Yoon, In-Ho; Kim, Alexandr; Lee, JungJun
Highlights: Operation experience for metal facilities for radioactive metal waste. The risk analys for operation of the metal facility. Considerations on operation and process of the melting facility. Considerations on design and configuration of the melting facility. Considerations on costs and safety of the melting facility. An approach to assessment in view of safety and regulation for operation of the melting facilities. Abstract: This paper is to provide an approach to safety assessment method prior to operation of the melting facility for radioactive metal waste from nuclear facilities. Operational experiences of metal facilities have been reviewed. Several technologies for melting have been analyzed and evaluated. It is important to be aware of the risks involved with the evolutionary development of technologies for operation of a melting facility. It is important to consult experienced operators to truly understand operating experience, limitations, and past problems before planning to invest in a given technology for operation of a melting facility. The operational experience of melting facilities has been reviewed and several technologies relevant with melting have been compared. A risk analysis for operation of a melting facility has been reviewed. The features of operation and design for a melting facility have been considered. Considerations in view of cost and safety have been taken and suggested. In view of regulation, operators and workers who have experienced well should be suitable for operation of a melting facility. In view of safety, all potential events should be analyzed for the facility, health for workers and the public, as well as impact on the environment according to their probability and consequence. Assessments should be performed by experts. It is expected that the suggested considerations could enhance the acceptability and safety for operation of nuclear melting facilities.